Spine pain during pregnancy [Gebelik döneminde omurga aǧrisi] - (:unkn) unknown (My University, 2005)
About more than 50 % of women suffer spine pain during and after pregnancy. Spine pain is simply classified into three groups; namely back pain , low back pain and pelvic pain. Although many factors are thought to be responsible for the pain, it's not clearly defined. This factors are physiologic and metabolic alterations leading to widening of symphysis pubis, intervertebral disc pathologies, postural and hormonal factors and changes in bone density. Among many mothers pain is relieved within few weeks after birth, however some may suffer even months. In this period of time, if the spine pain is thought to be due to physiologic alterations treatment modality is conservative. It must be always kept in mind that another underlying pathologic process is responsible for the pain and if necessary specific treatments should be given for this pathologies.
Keywords: Back Pain; Low Back Pain; Pelvic Pain; Postural Changes During Pregnancy